«Moral depreciation» of personal computer software as one of factors in reducing labor productivity at enterprise - E. V. Medvedev (Омский научный вестник: Серия "Общество. История. Современность", 2021)
In this article, the author examines the issue of «moral depreciation» of personal computer software and shows how it can affect the productivity of an organization. The relevance of the chosen topic is due to the fact that in the modern economy, with the advent of new products on the IT market aimed at optimizing work processes, low labor productivity is still observed in many companies, thereby arousing the interest of various researchers to understand this situation. The aim of the study is to analyze the processes of updating PC software at Russian enterprises and to study its impact on labor productivity. The main content of the study is the analysis of statistical data in the field of information and communication technologies in the context of various categories and groups. Special attention is paid to the analysis of the use of special programs at enterprises, as well as to the issues of personnel training on the use of these programs in their activities. As a result of the analysis, the author highlights the main points that arise in modern Russian companies due to the «moral depreciation» of software products, and also shows how they can affect their productivity. In conclusion, recommendations are offered to improve the current situation